Earthquake Potential Hazard Analysis of Palembang City, Sumatra Island - Triyoso, Wahyu; Suwondo, Aris; Naibaho, Zael Yahd Xanggam (Indonesian Journal on Geoscience, 2021)
Most of the destructive earthquakes in Sumatra are dominated by thrust mechanisms that occur due to the process of subduction and some earthquakes with strike-slip fault sources such as the Sumatra fault and northwestern Sumatra. The subduction zones along western Sumatra and Sumatran fault zones are active seismic sources of earthquake events. The seismotectonics of South Sumatra can be affected by earthquakes triggered by these seismic sources. In this study, an estimation and analysis of the potential for earthquake hazard curves were carried out in Palembang City due to the influence of subduction zone sources, strike-slip faults, and intermediate to deep earthquake sources. The algorithm of the seismicity smoothing was applied to estimate the seismicity rate for megathrust sources, active faults, and intermediate to deep earthquake sources. The results of the earthquake hazard potential curve showed that the estimated Peak Ground Acceleration (PGA) in the bedrock of the subduction earthquake sources was greater than the estimated ground shaking due to strike-slip fault sources as well as intermediate to deep earthquake sources. To understand better the potential ground shaking, the evaluation of PGA at the surface was then estimated by including the amplification factor. The amplification factor was calculated using the Horizontal-Vertical Spectral Ratio (HVSR) method. Based on the PGA estimated at the surface of 10% probability exceedance level during 50 years, the Palembang City has a potential shaking of around 35 gal, which is likely to be caused by a megathrust earthquake source.